Mercury vertical and horizontal concentrations in agricultural soils of a historically contaminated site: Role of soil properties, chemical loading, and cultivated plant species in driving its mobility. (15th September 2021) - Morosini, Cristiana; Terzaghi, Elisa; Raspa, Giuseppe; Zanardini, Elisabetta; Anelli, Simone; Armiraglio, Stefano; Petranich, Elisa; Covelli, Stefano; Di Guardo, Antonio
Abstract: The long term vertical and horizontal mobility of mercury (Hg) in soils of agricultural areas of a historically contaminated Italian National Relevance Site (SIN Brescia-Caffaro) was investigated. The contamination resulted from the continuous discharge of Hg in irrigation waters by an industrial plant (Caffaro S.p.A), equipped with a mercury-cell chlor-alkali process. The contamination levels with depth ranged from about 20 mg/kg dry weight (d.w.) of soil in the top (plow) layer to less than 0.1 mg/kg d.w. at 1 m depth. The concentrations varied also spatially, up to one order of magnitude within the same field and showing a decreasing trend from the Hg source (i.e., irrigation ditches). The concentration profiles and gradients measured were explained considering Hg loading, soil properties, such as the texture, organic carbon content, pH and cation exchange capacity. A Selective Sequential Extraction (SSE) was also applied on soil samples from an ad hoc greenhouse experiment to investigate the role of different plant species in influencing Hg speciation in soils. Although most of the extracted Hg was included in scarcely mobile or immobile forms, some plant species (i.e., alfalfa) showed to importantly increase the soluble and exchangeable fractions with respect to the unplanted control soils, thus affecting mobility and potential bioavailability of Hg. Graphical abstract: Image 1 Highlights: Mercury (Hg) was measured in soils of a highly contaminated agricultural area in Brescia, Italy. Contamination was due to the use of contaminated irrigation water from a chlor-alkali plant. Soil cores up to 1 m and spatial analysis evidenced gradients with depth and field length. A greenhouse experiment allowed to evaluate how plant species could change Hg speciation. Alfalfa importantly increased the soluble fractions of Hg and therefore its mobility in soil.